Pengaruh literasi keuangan dan kemampuan aritmetika sosial terhadap perilaku ekonomi mahasiswa - Umi Latifatul Amanah; Obi Rafli Mainaky (Jurnal Pendidikan Ekonomi (JUPE), 2026)
Student economic behavior is influenced by cognitive abilities in managing finances and understanding practical economic concepts. This study aims to analyze the influence of financial literacy and social arithmetic skills on the economic behavior of students at the Faculty of Economics and Islamic Business (FEBI) UIN Syekh Wasil, Kediri. The research method used a descriptive quantitative approach with a sample of 80 students from the Sharia Economics Study Program selected through simple random sampling. Data collection was conducted using questionnaires and tests, then analyzed using multiple linear regression techniques. The results showed that financial literacy had a positive and significant effect on student economic behavior, as did social arithmetic skills, which also had a positive and significant effect on student economic behavior. Simultaneously, both variables also had a significant effect on student economic behavior. This study concludes that financial literacy and social arithmetic skills are important cognitive foundations that contribute significantly to shaping students' economic behavior, improving financial decision-making abilities, and strengthening the analysis of daily economic conditions.